Wańkowicz and Contemporary War Movies. "Czerwone maki" (Red Poppies) Directed by Krzysztof Łukaszewicz - Nowakowski, Jacek (Porównania, 2025)
The article focuses on the contemporary cinematic context of Melchior Wańkowicz’s works by offering a comparative analysis of his books on the battle of Monte Cassino and the 2024 narrative film entitled Czerwone maki (Red Poppies). Investigating the free adaptation of the writer’s prose into a movie, the article poses questions whether and to what extent the movie draws from artistic attributes of Wańkowicz’s writing, and whether it is independent in its rendition of the historical event. The answer is not unequivocal, yet concludes that the movie lacks the personal emotional involvement and vivid imagery of Wańkowicz’s books. Instead, the narrative and semantic patterns of the film align with the commemorative nature of similar artistic ventures, thus bringing its informative and didactic functions to the foreground.